DAMPAK LIKUIDITAS, UKURAN PERUSAHAAN, DAN REPUTASI AUDITOR TERHADAP PENERIMAAN OPINI AUDIT GOING CONCERN - Hilmiyah, Siti; Dimyati, Muhaimin; Widaninggar, Nanda (Relawan Jurnal Indonesia, 2025)
Going Concern Audit Opinion is a statement given by the auditor to the company, where the company is able to maintain its business viability in the long term. This research aims to see or analyze the influence of Liquidity, Company Size and Auditor Reputation on the acceptance of Going Concern Audit Opinions simultaneously or partially. The population in this study obtained as many as 26 companies. Sampling using purposive sampling method and then the results obtained as many as 4 companies that have been determined according to the criteria. The analysis technique used is the logistic regression method. The results of the study indicate that there is no effect of Liquidity, Company Size and Auditor Reputation on the acceptance of Going Concern Audit Opinions simultaneously or partially.